Radiology during the Evaluation of Earthquake Survivors - Durmaz, Emine Sebnem; Kalyoncu Ucar, Ayse (Cerrahpaşa Medical Journal, 2023)
Earthquakes are one of the most devastating natural disasters, which may cause an unprecedented hazard to public health and the health system, depending on their intensity. Radiology has a central role in diagnosing and treating survivors who may have significant disorders directly related to the earthquake or its consequences. The trauma related to the earthquake may cause many disorders such as bone fractures, soft tissue and organ injuries, and both together. Moreover, infections are common in earthquake survivors who are mandated to live in non-optimal conditions. Hence, radiologists should be familiar with these complications and required imaging techniques. Digital radiography and computed tomography are the methods of choice to detect most earthquake-related disorders. In addition, ultrasonography also has its merits due to its diagnostic capability in soft tissue injuries and detection of pleural, pericardial, or intraperitoneal effusion. Besides, it is high reproducibility, feasibility, and availability rates. This review aimed to underline the radiological features of the most common complications in earthquake survivors. Cite this article as: Durmaz ES, Kalyoncu Ucar A. Radiology during the evaluation of earthquake survivors. Cerrahpaşa Med J. 2023;47(S1):72-74.